A THEORETICAL ANALYSIS OF THERMO- STONE'S BENEFITS COMPARED TO BRICKS AND OTHER FREQUENTLY USED BUILDING MATERIALS IN IRAQ - Jasim Jarallah Fahad Al-Kaabi; Suha Rasheed Abbas; Samer S. Abdulhussein (Journals Park Publishing, 2022)
According to the current study, the country urgently needs to build many housing units due to the country's growing population. This shift in the housing and construction industry mainly depends on the availability of substitute building materials with high-quality specifications, long lifespans, and reasonable costs. The cost of housing units has significantly increased due to my country's economic woes, economic crises, and rapid population growth (the population will reach roughly 40 million by 2030). The purpose of this study is to concentrate on the properties of thermo-stone Positive to construct units in Iraq that have good specifications, are ecologically benign, can be implemented quickly, and are less expensive than conventional materials. The study's conclusions were focused on some factors: lightweight, thermal and acoustic insulation, construction cost , resistant to moisture , speed of construction and Other building features.
Keywords: Population growth, high durability, thermo-stone, affordability, Benefits of Construction, and Materials Used Frequently in Iraq.